Growth performance of Calophyllum inophyllum in bioenergy trial plots in Bukit Soeharto Forest, East Kalimantan - Leksono, B.; Sukartiningsih; Windyarini, E.; Adinugraha, H.A.; Artati, Y.; Kwon, J.; Baral, H. (Center for International Forestry Research, 2022)
The Indonesian government has committed to providing its entire population with energy through the National Energy Policy, which highlights the importance of diversification, environmental sustainability, and enhanced deployment of domestic energy resources. The contribution of new and renewable energy (NRE) to the nation’s energy supply is mandated to reach 23% by 2025, with bioenergy an important NRE alternative. If developed and deployed appropriately, bioenergy plantations have potential to restore degraded land and enhance biodiversity and environmental services while supporting rural livelihoods. As a potential biofuel tree species suited to the tropics, Calophyllum inophyllum (nyamplung) is being tested across wide-ranging degraded forest conditions in Indonesia. Nyamplung is a potential biodiesel alternative as it grows well in harsh environmental conditions, produces non-edible seed oil, has high amounts of kernel oil and fruits profusely. Here we report growth performance in plantation trial plots established in February 2018, on previously burned land in Mulawarman University’s Bukit Soeharto Research and Educational Forest. Growth of this two-year old plantation is strong compared to other Indonesian sites, with average survival rate above 90% on Ultisol soil, which is classified as low fertility and acidic. The findings reveal that different doses of fertilizer applications and slope gradient have no significant effects on growth performance. In addition, trees have already started to flower and fruit, and are colonized by bird species and insects, including bees and butterflies.The study indicates that nyamplung adapts well to different land and soil types. Bioenergy plantations on degraded land are a promising approach for land restoration, and enhance native biodiversity and environmental services while providing a source of renewable energy.